Influence of different oxide thicknesses on the friction induced and continuous solid-state recycling of aluminum scrap - Gabsa, Steffen (Materials Research Proceedings)
Abstract. Saving emissions and a circular economy are key aspects of sustainable production and compliance global climate change targets. Friction-induced solid-state recycling of aluminum scrap to production endless semi-finished products. Scrap is fed into a continuously rotating wheel. This requires less energy compared to heat-based recycling processes. Different sizes, shapes and surfaces of chips can be used as starting material in the process. The influence of this has been shown in past publications. A native oxide layer is a fixed component of aluminum surface. This layer is broken up during the forming process, allowing the aluminum to bond. In addition to the geometry, the surface finishes and the thickness of the oxide layer are therefore also important input variables in friction-induced solid-state recycling. The oxide layers on the chips were determined for the investigation. In addition, different layer thicknesses were produced to survey their influence. The resulting semi-finished products were evaluated on the basis of their tensile strength and microstructure. The main result of the investigations is the fact that semi-finished products made from chips with thicker oxide layers tend to be more brittle. In addition, thick oxide layers cause microstructural and surface defects.